2016
DOI: 10.1021/acs.chemmater.6b02953
|View full text |Cite
|
Sign up to set email alerts
|

Designing Fe-Based Oxygen Catalysts by Density Functional Theory Calculations

Abstract: Figure S1. The highest symmetry is used for placing the substitution elements. Images are produced by VESTA 1 .Figure S1. Structure models for A site substitution (a) and B site substitution (b).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 63 publications
3
34
1
Order By: Relevance
“…2e . More negative E vf-O value implies easier formation of oxygen vacancies in the reduction environment 35 . The E vf-O value becomes more negative after doping Sr 2+ into Ba 2+ , revealing that the Sr 2+ doping facilitates the formation of oxygen vacancies in the reduction atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…2e . More negative E vf-O value implies easier formation of oxygen vacancies in the reduction environment 35 . The E vf-O value becomes more negative after doping Sr 2+ into Ba 2+ , revealing that the Sr 2+ doping facilitates the formation of oxygen vacancies in the reduction atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Recent DFT calculations showed that in the case of Fe‐based perovskite (AFeO 3 ), the presence of divalent alkaline‐earth metal cations (i.e., Ca, Sr, and Ba) in A‐site, relative to the lanthanides (in A‐site), substantially lowers the E vac from 3.73 eV to 0.90–1.37 eV . Chen et al surveyed A‐ and B‐site elements that can be incorporated as dopants into BaFeO 3 perovskite framework and studied how the substitution may influence the electronic properties, oxygen vacancy formation, and oxygen migration within these materials . Similar study into Ruddlesden–Popper phases of Ln 2 NiO 4+ δ has also been performed …”
Section: Prediction Of Intrinsic Properties Of Materials By Dft Calcumentioning
confidence: 99%
“…All lattice constants of Ba 1¹x La x FeO 3¹¤ were less than 4.02 ¡, which is in agreement with the lattice constants evaluated from first principle calculations. 20), 21) The specimen with a nominal composition of BaFe 0.9 -La 0.1 O 3¹¤ was a mixture of cubic and other phases. The lattice constant of the cubic phase, depicted by the closed red reverse triangle in Fig.…”
Section: Resultsmentioning
confidence: 99%